2016
DOI: 10.1016/j.aju.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of renal recovery in renal failure secondary to bilateral obstructive urolithiasis

Abstract: ObjectivesTo identify factors predicting renal recovery in patients presenting with renal failure secondary to bilateral obstructing urolithiasis.Patients and methodsData from electronic records of consecutive adult patients presenting with bilateral obstructing urolithiasis between January 2007 and April 2011 were retrieved. Ultrasonography of the abdomen, and kidney, ureter, bladder (KUB study) X-ray or abdominal non-contrast computed tomography confirmed the diagnosis. Interventional radiologists placed bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
4
7
1
Order By: Relevance
“…Also, the incidence of mucosal injury and ureteral perforation was increased in upper ureteric stones, stone size >1.5 cm and anuric period of 3 days, which was consistent with findings of Yossepowitch et al ., Varda et al ., Savic et al . and Rajadoss et al 17–20 . PCN insertion failure and pelvic extravasation were more likely to occur in cases of mild HN and renal stone size >2.5 cm, which was consistent with the findings of Sommer et al .…”
Section: Discussionsupporting
confidence: 88%
“…Also, the incidence of mucosal injury and ureteral perforation was increased in upper ureteric stones, stone size >1.5 cm and anuric period of 3 days, which was consistent with findings of Yossepowitch et al ., Varda et al ., Savic et al . and Rajadoss et al 17–20 . PCN insertion failure and pelvic extravasation were more likely to occur in cases of mild HN and renal stone size >2.5 cm, which was consistent with the findings of Sommer et al .…”
Section: Discussionsupporting
confidence: 88%
“…On average, the preoperative SCr was 6.13 ± 3.2 mg/dl. It had no statistically significant effect the improvement in SCr which was similar to the results [18][19][20]. However, it was different from the previous results found that the low SCr at presentation was a statistically significant predictor for recoverability of renal functions in patients with Po-AKI [5,14,21].…”
Section: Discussionsupporting
confidence: 74%
“…The latter processes are usually reflected on the patient's physical conditions, functional performance, and they can competently compensate for the pathophysiological sequels of AKI after drainage. These functional competences may help making a decision of invasive interventions such as JJ placement [1,6,18,19]. This is in contrast with patients with MUO who have bad general performance and short life expectancy due to the advanced malignancy [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged obstruction and comorbidity like hypertension will lead to non-functioning kidney units that ultimately ended up with nephrectomy. 24 In our study, 20(29.41%) Patients with non-functioning kidneys, underwent nephrectomy.…”
Section: Discussionmentioning
confidence: 66%